Preservation of Cross-strata Due to Migration of Subaqueous Dunes Over Aggrading and Non-aggrading Beds: Comparison of Experimental Data with Theory - Leclair, Suzanne; Bridge, John; Wang, Feiqiao (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1997)
Summary An experimental study of the preservation of cross strata during the migration of dunes under aggrading and non-aggrading conditions was conducted inorder to test the Paola-Borgman (1991) theory for distribution of cross-set thickness as a function of the distribution of bed-wave height. The theory needed to be modified to deal with aggrading conditions (Bridge and Best, 1997). The geometry and migration characteristics of the dunes (determined using an ultra-sonic depth profiler and visual observations) are typical of sinuous-crested dunes observed in rivers and other flumes.These characteristics do not vary systematically with aggradation rate. As part of the test of theory, a two-parameter gamma density function was fitted to histograms of dune height and dune trough elevations relative to two different reference datums. The parameters of these fitted functions do not vary in the way predicted by Paola and Borgman because: 1) dune height does not correlate very well with dune trough elevation, and; 2) choice of reference datum has amajor, unanticipated effect on parameter values. Most cross sets were formed by only the highest 10% of the dunes. Meancross-set thickness/mean formative bed-wave height ranges from 0.18 to 0.3.Cross-set thickness does not vary systematically with aggradation rate in these experiments because the primary control of set thickness is the variability of dune height. Mean cross-set thicknessis predicted quite well using the modified Paola-Borgman theory if:1) dune height is used as a proxy for dune trough elevation but certain parameter values are modified, or; 2) an appropriate datum is used for defining dune trough elevations. A simple method is proposed for estimating the height distribution of dunes from the thickness of their sets of medium-scale cross strata.